One Shot, Zero Risk: Strategi Pintar Mencegah Infeksi dari Penyuntikan - Afifah, Laili; Salsabila, Nadya Seika; Azzahra, Revadina Nazwa; Agita, Yasha; Afifah, Rahma Nur; Aulia, Bulan; Mufida, Azzura; Monika, Elma; Astuti, Tania Dwi; S, Sudiharto (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
One Shot, Zero Risk: A Smart Strategy to Prevent Injection-Related Infections is a health education activity conducted on October 17, 2025, aimed at increasing students’ knowledge about safe injection practices and the six rights of medication administration. Background: Infections caused by unsafe injections remain a risk in healthcare facilities. Nursing students need to be equipped with proper understanding and skills in injection techniques according to patient safety standards. Method: The activity applied an educational and participatory approach through interactive lectures, discussions, demonstrations, and simulations at Mulia Karya Husada Health Vocational School. Evaluation was carried out using pre-test and post-test assessments on 30 students to measure improvements in knowledge and preventive attitudes. Results: The students’ average scores increased from 65% to 92% after the intervention, indicating a significant improvement in understanding safe injection principles and applying the six rights of medication administration. Students also showed positive behavioral changes, becoming more cautious, responsible, and patient-safety oriented. Conclusion: This program proved effective in enhancing knowledge and fostering a culture of patient safety from an early stage. Practice-based education is recommended to be continuously implemented in health education settings to prevent infections and clinical procedure errors.